Diagnosis of Autoimmune Hepatitis using International Autoimmune Hepatitis Group Scoring - Sigit Triyus Priyantoro; Harijono Ahmad (The Indonesian Society for Digestive Endoscopy, 2013)
Autoimmune hepatitis (AIH) is described as T lymphocyte suppressor disturbance, thus there is formation of autoantibody which attacks surface antigen of liver cells or hepatocytes. Diagnosis of AIH is done after other liver abnormalities have been ruled out. The diagnosis of AIH needs to be done with thorough and careful examination as there is no pathognomonic clinical appearance.Autoimmune hepatitis (AIH) is described as T lymphocyte suppressor disturbance, thus there is formation of autoantibody which attacks surface antigen of liver cells or hepatocytes. Diagnosis of AIH is done after other liver abnormalities have been ruled out. The diagnosis of AIH needs to be done with thorough and careful examination as there is no pathognomonic clinical appearance.Keywords: autoimmune hepatitis, asymptomatic, increased transaminase